Can early-onset acquired demyelinating syndrome (ADS) hide pediatric Behcet's disease? A case report - Pozzato, Mattia; Dilena, Robertino; Rogani, Greta; Beretta, Gisella; Torreggiani, Sofia; Lanni, Stefano; Tozzo, Alessandra; Andreetta, Francesca; Cavalcante, Paola; Triulzi, Fabio; Martinelli Boneschi, Filippo; Minoia, Francesca; et al. (Frontiers in Pediatrics, 2023)
Behcet’s disease (BD) is a rare vasculitis characterized by multisystemic inflammation. Central nervous system (CNS) involvement is rare and heterogeneous, particularly in the pediatric population. Diagnosis of neuro-Behcet could be highly challenging, especially if neurological manifestations precede other systemic features; however, its timely definition is crucial to prevent long-term sequelae. We describe the case of a girl who presented, at 13 months of age, with a first episode of encephalopathy compatible with Acute Disseminated Encephalomyelitis, followed after six months by a neurological relapse characterized by ophtalmoparesis and gait ataxia in association with new inflammatory lesions in the brain and spinal cord, suggesting a Neuromyelitis Optica Spectrum Disorder. The neurological manifestations were successfully treated with high-dose steroids and intravenous Immunoglobulins. In the following months, the patient developed a multisystemic involvement suggestive for Behcet’s disease, characterized by polyarthritis and uveitis, associated with HLA-B51 positivity. The challenge of this unique case required a multidisciplinary approach including pediatric neurologists, neuro-radiologists and pediatric rheumatologists, and each specialist increased awareness about early-onset acquired demyelinating syndromes (ADS). Given the rarity of this presentation, we performed a review of the literature focusing on neurological manifestations in BD and differential diagnosis of patients with an early onset ADS.